“Far From Uninteresting”: Getting to Know the St. Lawrence River at Montreal During the Construction of the Victoria Bridge - Braiden, Heather (Urban History Review/Revue d'histoire urbaine, 2022)
In northern cities like Montreal, Quebec, Canada, the winters are long, and the construction season is condensed. In the mid-nineteenth century, knowing the St. Lawrence River’s seasonal variations and local construction customs helped railway and bridge builders save time and frustration during the very short working seasons. In this article, I investigate how technical and quasi-technical communications generated during the construction of the Victoria Bridge (1854–1860) are a rich source of urban knowledge. By examining visual and textual evidence in The Construction of the Great Victoria Bridge in Canada, I demonstrate how representations of the construction process are a tangible medium through which practical experience and a personal way of knowing the urban landscape are mediated. I argue that everyday experience and tacit knowledge move between social worlds and inform how audiences know and understand the colonial city.
Keywords: Victoria (pont)

Les déterminants de la valeur dans le marché immobilier montréalais: étude appliquée aux lignes de distribution câblées, à la végétation et aux types de rue - Montpetit, Guillaume (Université du Québec à Montréal, 2010)
Keywords: Logement; Quartiers; Île-des-Soeurs

Les années de dispersion - Fougères, Dany (Histoire de Montréal et de sa région, 2012)
Keywords: Côtes; Fortifications; Logement; Notre-Dame (paroisse); Routes; Rues; Villages

The years of dispersion - Fougères, Dany (Montreal: The History of A North American City, 2018)
Keywords: Côtes; Fortifications; Logement; Notre-Dame (paroisse); Routes; Rues; Villages

Soutien et entraide. Les mouvements coopératifs et communautaires du Plateau de 1970 à 2000 (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2021)
Keywords: Clinique des citoyens de Saint-Jacques; Cyclisme; Groupes populaires; Logement; Plateau Mont-Royal; Quartiers

Le pont du domaine Saint-Gabriel - Douaire, Gilles (Histoire Québec, 2011)
Keywords: Communautés religieuses; Lachine (canal); Ponts; Saint-Gabriel (ferme); Seigneurie; Sulpiciens; Séminaire

Repurposing buildings (The Westmount Historian, 2016)
Keywords: Conservation; Gares; Logement; Patrimoine

WHA looks at some Prominent Westmounters (The Westmount Historian, 2008)
Keywords: Lait; Magasins; Port; Quartiers; Quincaillerie; Westmount

Montreal 1960: The Singularities of a Metropolitan Archetype - Lortie, André (The 60s: Montreal Thinks Big, 2004)
Keywords: Métropole

Montréal 1960; les singularités d'un archétype métropolitain - Lortie, André (Les années 60: Montréal voit grand, 2004)
Keywords: Métropole

1840-1912: De la montée du Sault à la rue Lajeunesse: sept décennies de chemins de barrières... et quelques incendies - Lebleu, Jacques (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2019)
Keywords: Incendies; Routes; Rues

Victoria Avenue in Westmount (The Westmount Historian, 2010)
Keywords: Casernes; Gares; Logement; Magasins; Rues; Westmount; Épicerie

La requalification du secteur industriel du Mile End, Montréal - Bur, Justin (Bulletin de l'AQPI, 2022)
Keywords: Canadien Pacifique; Carrière; Chemins de fer; Mile End

BÉÏQUE, FRÉDÉRIC-LIGORI - Vallières, Marc (Dictionnaire biographique du Canada, 2022)

Saint-Louis-Du-Mile-End. De la campagne à la ville (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2023)
Keywords: Chemins de fer; Institution des sourds-muets; Logement; Mile End; Soeurs de la Providence

DAWSON, ARTHUR OSBORNE - Miller, Carman (Dictionnaire biographique du Canada, 2023)